Development of Interactive Media Based on Lectora Inspire Solar System (SITAYA) to Material to Increase Students Learning Motivation in Science - Triastika, Adinda Yaniar; Tyas, Dewi Nilam (Jurnal Pijar Mipa, 2025)
Success in learning is important, not only influenced by student intelligence, but also by learning environment factors, motivation, learning styles, methods, strategies and learning media, these factors greatly influence student learning outcomes. This study aims to develop and test the feasibility and effectiveness of interactive learning media based on Lectora Inspire, specifically SITAYA (Solar System), in order to enhance the motivation and learning outcomes of sixth-grade students at SDN 4 Honggosoco in the Natural and Social Sciences (IPAS) subject, focusing on the solar system. The method used in this study is research and development, utilising the ADDIE model, which is simplified into five distinct stages. The validation process was conducted by media experts and material experts, resulting in assessments of 80% and 83.92%, respectively. This is supported by the results of student and teacher responses, with a percentage of 88.88% and 96.66%, respectively. Based on the results of the learning motivation questionnaire, it can be concluded that the category is very good, with a percentage of 98.8%. The effectiveness test, conducted using a one-group pretest-posttest design, showed a significant increase in the average score of students, from 42.61 to 83.65. The results of the paired t-test showed a significance value of 0.000 (<0.05), indicating a statistically significant increase. The N-gain calculation of 0.71 indicates a high level of effectiveness. SITAYA media is declared feasible and effective in supporting interactive and meaningful science learning. Additionally, SITAYA media is also highly effective in increasing student motivation and learning outcomes. These findings support the use of Lectora Inspire technology as an innovative solution in science learning at the elementary school level.